Molecular composition and biodegradation of loggerhead sponge Spheciospongia vesparium exhalent dissolved organic matter. (December 2020) - Letourneau, Maria L.; Hopkinson, Brian M.; Fitt, William K.; Medeiros, Patricia M.
Abstract: Sponges are critical components of marine reefs due to their high filtering capacity, wide abundance, and alteration of biogeochemical cycling. Here, we characterized dissolved organic matter (DOM) composition in the sponge holobiont exhalent seawater of a loggerhead sponge ( Spheciospongia vesparium ) and in ambient seawater in Florida Bay (USA), as well as the microbial responses to each DOM pool through dark incubations. The sponge holobiont removed 6% of the seawater dissolved organic carbon (DOC), utilizing compounds that were low in carbon and oxygen, yet high in nitrogen content relative to the ambient seawater. The microbial community accessed 7% of DOC from the ambient seawater during a 5-day incubation but only 1% of DOC from the sponge exhalent seawater, suggesting a decrease in lability possibly due to holobiont removal of nitrogen-rich compounds. If this holds true for other sponges, it may have important implications for DOM lability and cycling in coastal environments. Highlights: S. vesparium holobiont altered the DOM composition of seawater in Florida Bay. Sponge-microbial holobiont uptook 6% of DOC from ambient seawater. Compounds with low carbon, low oxygen, and high nitrogen content were depleted. Sponge exhalent water was enriched in large, more aromatic compounds. Microbial consumption of DOC was higher in seawater than in sponge exhalent water.